Scalp and face edema in Schönlein-Henoch syndrome - Çağlar, Musa Kâzım; Arsoy, Emin Sami (The Turkish Journal of Pediatrics, 1983)
Scalp and face edema are described in two patients with Schönlein-Henoch syndrome. In one, abdominal pain and swelling of the face and scalp were noted for one week prior to the onset of the rash and joint involvement, and in the other swelling was seen seven days after the rash. We believe that the possibility of anaphylactoid purpura should be considered in the differential diagnosis of children with abdominal pain and localized edema on the head prior to the onset of rash. Antihistaminic agents seemed to be useful in the relief of edema.